Rios urbanos e o processo de urbanização : o caso de Passo Fundo-RS - Corazza, Jaqueline (2008)
This present work is an analysis of urban rivers and of the urbanization process of the town of Passo Fundo, located in the north of the state of Rio Grande do Sul Brazil. It is attempted to rescue the fact that the course of the humanity History passes through the rivers bed, and many cities grew up at their margins. Then, they are, currently, disregarding these rivers, changing them into forgotten landscapes, as well as changing a public environmental heritage into a private one. This study is based on the analysis of the urbanization, on the comparison of the situation of the water courses in 1953 and 2007, by means of a diagnosis in loco through the water courses. The field survey was carried out in six sectors, including photographic survey, records in spreadsheets and informal interviews. The indicators used were the fragmentation and the use of the soil, the pattern of the buildings, the environmental and urbanization impacts, the service to the environmental legislation, the existence of vegetation, the permeability of the soil and the landscape formed in these spaces. It was observed that the relation of the rivers with the town of Passo Fundo is problematic. From the diagnosis of the sectors, it was observed that 60% of the study areas passages are chanelled, with landfill on the bed, inefficiency of the drainage system. On the non chanelled water courses, it was possible to observe irregular occupation, sewage launch, accumulation of waste, suppression of vegetation making landscape degraded. It was observed the inapplicability of the environmental and urbanistic legislation. An area for preparation of a Pilot Project, a Linear Park along the Passo Fundo River, were defined, working with urbanized and non urbanized areas. The project delimits the area of the park, defines the territorial appropriation in the short and medium term, suggests use and zoning for the park. The results, recommendations and directives were grouped as for the system of information, as for the legislation service, the territorial occupation and the landscape of the margins of urban rivers. The issue for the urban area of Passo Fundo was emphasized, but presenting, in such a way that it is possible to be applied in other cities with similar situations. The territorial occupation of Permanent Preservation Areas of the urban rivers margins must be planned, combining the urban focus to the environmental one, making the landscapes visible and changing them, priority leisure areas